Ligustilide Attenuates Ischemia Reperfusion-Induced Hippocampal Neuronal Apoptosis via Activating the PI3K/Akt Pathway - Wu, Qian; Mao, Zhiguo; Liu, Jiao; Huang, Jinling; Wang, Ning (Frontiers in Pharmacology, 2020)
Ligustilide (LIG), a main lipophilic component of the umbelliferae family of pharmaceutical plants, has been shown to exert neuroprotective effects in mitigating cerebral ischemia injury and apoptosis. We investigated mechanisms underlying the anti-apoptotic effects of LIG in vitro and in vivo, respectively, using cultured primary hippocampal neurons and rats under oxygen-glucose deprivation/reperfusion (OGD/R) conditions. In vitro studies revealed that the suppressed apoptosis in hippocampal neurons upon LIG treatment was associated with reduced calcium influx and generation of reactive oxygen species. The LIG-treated hippocampal neurons exhibited decreased expression of cleaved caspase-3, Bax and decreased release of CytC from mitochondria, which were accompanied with increased expression of Bcl-2 and enhanced phosphorylation of AKT, in a PI3K-dependent manner. In vivo studies demonstrated a neuroprotective role of LIG in attenuating cerebral infarction volume, neurological injury and apoptosis, suggesting that LIG could reverse ischemia reperfusion(I/R)-induced hippocampal neurons apoptosis. These results together suggest that the natural compound LIG may be considered as a neuroprotective agent in the treatment of ischemia stroke.